REKONFIGURASI JARINGAN DISTRIBUSI 20 KV UNTUK PERBAIKAN PROFIL TEGANGAN DAN SUSUT DAYA LISTRIK - Prasetijo, Hari (UMP, 2010)
This study was conducted to evaluate the voltage profile and decrease the electric power, main feeder 20 kV distribution system of Kalibakal Substation (GI Kalibakal). Evaluation refers to the standard PT. PLN (Persero) SPLN 72: 1987 about the specification and design to JTM and JTR and SPLN 10-1A: 1996 percentage losses tolerance is ± 10% of the power delivered. Evaluation results used as the basis for improved simulation voltage drop and power losses with a network reconfiguration method. Potential re-configuration is determined by looking at the voltage profile and power losses in each configuration feeder and around feeder nearest feeder that will be reconfiguration. Simulation is done using the tools ETAP power station to analyze the power flow the main feeder of GI Kalibakal.The first simulation assuming GI Kalibakal voltage of 20 kV as the voltage rating of medium voltage distribution system. The result is that the voltage profile, 92.66% in feeder 5 and 94.62% in feeder 6 under standard. With the GI Kalibakal boost to the 20.5 kV, voltage profile feeder 5 rose to 95.29% and feeder be 97.21% 6. So by increasing the voltage GI Kalibakal from 20 kV to 20.5 kV voltage profile already meet the standards.From the simulation with the GI Kalibakal voltage 20.5 kV, losses that occur in all feeder under 10% which means meet with the standard, the largest losses in feeder 5 for 2.81%. Losses had to be suppressed as small as possible in this case performed by a network reconfiguration that can be done without investment. Reconfiguration is done by involving feeder 2, 3, 5 and 6 with total losses before the reconfiguration is 401 kW. After a reconfiguration of the steps:1. Three sections with a value of voltage on the marginal area (section 5_8, section5_9 and 5_10) feeder delegated to section 6 through 6_8, 2. Section 6_11 and 6_12 section feeder transferred to section 3 through 3_6, 3. Section 5_8, 5_9 and 5_10 its section 6_8, 6_9 and 6_10 delegated to feeder section 2 through 2_6, total losses feeder 2,3,5 and 6 to 290 kW, so there is a decrease losses of 401-290 = 111 kW. Key word : Reconfiguration, voltage profile, losses.